The Position of Daughters in Batak Customary Inheritance Law from the Perspective of Islamic Law - Apriliani; Tjempaka, Tjempaka (Jurnal Mahkamah : Kajian Ilmu Hukum dan Hukum Islam, 2025)
This study aims to examine how the Batak Muslim community reconciles the conflict of values between the patrilineal customary inheritance system and egalitarian Islamic inheritance law regarding women's inheritance rights. The method used is normative juridical with qualitative analysis of laws and regulations such as the Compilation of Islamic Law, customary law, and legal doctrines and expert views. Data were collected through literature studies from primary, secondary, and tertiary sources. The results of the study show that the Batak customary system places sons, especially the eldest, as the main heirs, while daughters formally do not have inheritance rights. Meanwhile, Islamic law grants inheritance rights to women with a certain portion based on socio-economic responsibility. The tension between these two legal systems creates social and legal dilemmas for the Batak Muslim community. In practice, various reconciliation strategies emerge, such as granting grants or wills to daughters before the testator dies to balance customary values and Islamic law. This study emphasizes the importance of a contextual and participatory approach in harmonizing customary norms and religious law for the sake of justice and social acceptance.